The Mediating Effect of Motivation and Job Satisfaction Between Work Environment and the Performance of Judges and Court Clerks in Riau Islands Province - David Tan; Lily Sudhartio (Universitas Bunda Mulia, 2021)
The objective of this research is to distinguish the effect of work environment on the performance of judges and court clerks in the Riau Islands Province of Indonesia, and the impact of motivation and job satisfaction as intervening variables in influencing the model. A census questionnaire was produced and validated employing a pilot data. A total of 109 questionnaires were distributed to judges and court clerks in Riau Island Province and all questionnaires were returned and validated. Regression was utilised to predict and measure the correlations; thus, the outcomes statistically suggest that there are a meaningful and positive impact in the model. The mediation test indicates that motivation and job satisfaction act as mediating variables (partial mediation) and mediate the relationship between the work environment and the performance of the judges and court clerks. This research implies that a good working atmosphere results in a better motivation and job satisfaction that boosts the working performance. Judges and court clerks enjoy considerable benefits if the determinant were being addressed. This study has extended the existing literature by identifying the mediating role of motivation and job satisfaction on determinants affecting work performance of judges and court clerks, specifically in the Indonesian context.